Correction: Li et al. Fringe Projection Profilometry Based on Saturated Fringe Restoration in High Dynamic Range Scenes. Sensors 2023, 23, 3133 - Hongru Li; Hao Wei; Jiangtao Liu; Guoliang Deng; Shouhuan Zhou; Wenwu Wang; Liang He; Peng Tian (Sensors, 2023)
The authors wish to make the following corrections to the original paper [...]